Bypassing the Supercrip Trope in Documentary Representations of Blind Visual Artists - Catalin Brylla (Disability Studies Quarterly, 2018)
Mainstream narratives depicting blind people who create visual art have repeatedly used the supercrip trope. For a seeing audience this trope highlights an artist's extraordinary skill and perseverance in creating aesthetic artefacts despite lacking – what is presumed to be – the essential sensory input of sight. This type of representation fails to portray the diversity and complexity of individual character traits but conveniently places blindness at the story's center; this turns the artistic process into a simplistic manifestation of 'abnormality' and 'otherness'. My own documentary practice explores filmic strategies that bypass the supercrip trope by emphasizing the 'everydayness' of the artistic creation process. The aim is for a seeing audience to experience the creation process as an ordinary, everyday act – amongst many others – in which blindness is neither foregrounded nor 'backgrounded'. This is illustrated through discussion of my documentary The Terry Fragments (2018), a film that represents a blind artist's painting process through narrative fragments and the depiction of improvisation and failure. These strategies evoke the multi-layered and heterarchical plurality of everydayness, which potentially resists the formation of the supercrip trope. This method can be applied to a variety of disability contexts that are prone to perpetuating the supercrip stereotype.